Malignant rhabdoid tumor of the liver: a case report and literature review - Satoru Oita; Keita Terui; Syugo Komatsu; Tomoro Hishiki; Takeshi Saito; Tetsuya Mitsunaga; Mitsuyuki Nakata; Hideo Yoshida (MDPI AG, 2015)
Malignant rhabdoid tumor (MRT) is a rare and aggressive malignancy associated with poor outcomes. MRT of the liver is even rarer, and little information has been described. We report the case of an 8-month-old boy with MRT of the liver. The tumor showed aggressive progression despite a multidisciplinary approach, and the patient died due to multiple organ failure 14 days after admission. Autopsy revealed the liver tumor and multiple metastases with negative immunohistochemistry for INI1/BAF47. A review of 53 cases of pediatric MRT of the liver is provided.